Reconstructing Islamic Governance Through Maqasid Al-Shariah - Muhammad Alfi Syahrin; Khoiriyah; Heri Rifhan Halili; Babussalam (PT. Education Research Center, 2025)
This conceptual article reconstructs Islamic governance through maqasid al-Shariah by shifting the focus from formal compliance to public value, institutional trust, and measurable maslahah. Contemporary governance in Muslim societies is often trapped between procedural modernity and symbolic religiosity: institutions may display Islamic labels while policy design, accountability, and public welfare remain weak. The study therefore asks how maqasid al-Shariah can be translated into a practical governance framework for law, policy, finance, and public administration. Using an integrative literature review and maqasidi hermeneutic analysis, this article synthesizes recent studies published between 2021 and 2026. The analysis identifies four findings. First, Islamic governance requires a normative anchor that joins tawhid, amanah, justice, shura, and ihsan with contemporary principles of transparency, participation, and evidence-based policy. Second, maqasid must be operationalized as indicators of protection, empowerment, and flourishing, not merely as abstract legal objectives. Third, a reconstructed model should connect rule legitimacy, institutional capability, ethical leadership, and public accountability. Fourth, the maqasid approach expands governance evaluation beyond economic growth toward human dignity, social justice, environmental stewardship, and intergenerational welfare. The article contributes a maqasid governance matrix and an implementation cycle that can guide future empirical research and policy evaluation in Muslim-majority and minority contexts.